Grenzleben in Ceuta und Melilla - Mehlmer, Sara (Brill, 2025)
Sara Mehlmer's microhistorical study offers surprising insights into the actions of Spanish actors in the enclaves of Melilla and Ceuta. Life in these enclaves at the end of the 19th century was characterized not only by numerous antagonisms and conflicts, but also by repeated contact and cooperation. Due to its unique location, this region between Europe and Africa, Spain and Morocco, Christianity and Islam seemed to harbor enormous potential for conflict. Yet, it was precisely this border location that not only led to confrontation and isolation, but also necessitated the establishment of conflict resolution strategies and fostered cross-border contacts. The situational weighting of various categories of difference—including religion, nation, ethnicity, and gender—and the associated more or less flexible handling of these categories at both the institutional and individual levels played a significant role in this process.